Skin cancer and chronic mucocutaneous candidiasis. - Berloco, A.; Tsou Tsou, A.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2002)
Two cases of skin cancer in subjects with chronic mucocutaneous candidiasis (CMCC) are reported. Moreover, the relationship between CMCC, skin cancer and immune deficiency are discussed.